Penatalaksanaan Fourniers Ganggrene pada Area Skrotum dengan Diabetes Mellitus Tipe II - Sustantine Restiany, Helen; Sustantine Totalia, Lely; Anthony, Willy; Taba Parinding, Imanuel (CV. Jasa Sukses Abadi, 2024)
Fournier's Gangrene (FG) is a rare but progressive and life-threatening necrotizing fasciitis (NF) with a prevalence rate of approximately 1.6 cases per 100,000 males annually. FG is often caused by polymicrobial infections, with common sources being urological diseases in the perianal region. A 35-year-old male presented with a painful boil in the lower scrotal area. The lesion ruptured, discharging pus mixed with blood and emitting a foul odor. The wound progressively enlarged, extending from superficial layers to the peripheral nervous system. The patient had a one-year history of diabetes mellitus (DM) with an HbA1C of 7.8% and a random blood glucose level of 98 mg/dL. Based on culture, radiological, and laboratory findings, a diagnosis of scrotal FG was established. The patient underwent debridement from the scrotum to the abdominal wall, including both iliac regions. Regular post-debridement wound evaluations were conducted to ensure the removal of necrotic tissue. Broad-spectrum antibiotics, such as ceftriaxone and metronidazole, were administered to reduce systemic toxicity, inhibit infection progression, and eliminate causative microorganisms. Early and radical debridement of necrotic and non-viable tissue is crucial in halting infection progression, especially in patients with type 2 DM. The cornerstone of FG management includes hemodynamic stabilization, systemic broad-spectrum antibiotic therapy, and surgical debridement. Supportive care, such as hyperbaric oxygen therapy, may be beneficial in certain FG cases. The mortality rate for FG is considerably high, with studies indicating rates ranging from 17% to 28% in Indonesia. Diabetes mellitus and infections with Clostridium perfringens have been identified as independent risk factors for in-hospital mortality among male FG patients. FG is a medical emergency requiring prompt diagnosis and aggressive treatment, including surgical debridement and broad-spectrum antibiotics. Early intervention is essential to improve patient outcomes.